How to read a photograph understanding, interpreting and enjoying the great photographers - Jeffrey, Ian 1942- (Thames & Hudson, 2008)
Ian Jeffrey is an excellent guide in this profusely illustrated introduction to the appreciation of photography as an art form. Novices & experts alike will gain a deeper understanding of great photographers & their work, as Jeffrey decodes key images & provides essential biographical & historical background.